Carriage of CTX-M type extended spectrum β-lactamases (ESBLs) in gulls across Europe. Issue 1 (December 2015) - Stedt, Johan; Bonnedahl, Jonas; Hernandez, Jorge; Waldenström, Jonas; McMahon, Barry; Tolf, Conny; Olsen, Björn; Drobni, Mirva
Abstract Background Extended spectrum β-lactamases (ESBLs), a group of enzymes conferring resistance to third generation cephalosporins have rapidly increased inEnterobacteriacae and pose a major challenge to human health care. Resistant isolates are common in domestic animals and clinical settings, but prevalence and genotype distribution varies on a geographical scale. Although ESBL genes are frequently detected in bacteria isolated from wildlife samples, ESBL dissemination of resistant bacteria to the environment is largely unknown. To address this, we used three closely related gull species as a model system and collected more than 3000 faecal samples during breeding times in nine European countries. Samples were screened for ESBL-producing bacteria, which were characterized to the level of ESBL genotype groups (SHV, TEM), or specific genotypes (CTX-M). Results ESBL-producing bacteria were frequently detected in gulls (906 of 3158 samples, 28.7 %), with significant variation in prevalence rates between countries. Highest levels were found in Spain (74.8 %), The Netherlands (37.8 %) and England (27.1 %). Denmark and Poland represented the other extreme with no, or very few positive samples. Genotyping of CTX-M isolates identified 13 different variants, withbla CTX-M-1 andbla CTX-M-14 as the most frequently detected. In samples from England, Spain and Portugal, bla CTX-M-14 dominated, while in the rest of the sampled countriesbla CTX-M-1 (except Sweden wherebla CTX-M-15 was dominant) was the most frequently detected genotype, a pattern similar to what is known from studies of human materials. Conclusions CTX-M type ESBLs are common in the faecal microbiota from gulls across Europe. The gull ESBL genotype distribution was in large similar to published datasets from human and food-production animals in Europe. The data suggests that the environmental dissemination of ESBL is high from anthropogenic sources, and widespread occurrence of resistant bacteria in common migratory bird species utilizing urban and agricultural areas suggests that antibiotic resistance genes may also be spread through birds.